Extraction and Characterization of Astaxanthin from Processed Rebon Shrimp Products as a Local Wisdom-Based Antioxidant Source - Delia Ramadhina Tanzikha; Anis Shofiyani; Winda Rahmalia; Dwi Imam Prayitno; Intan Syahbanu; Syarifah Jubaidah; Titik Lestari (Jurnal Kelautan Tropis, 2026)
Astaxanthin, a carotenoid with pronounced antioxidant properties, represents a promising candidate for development as a functional food ingredient grounded in local wisdom. Traditional rebon shrimp derivatives including dried rebon, terasi, and cincalok are recognized sources of this pigment; however, systematic data on extraction efficiency, astaxanthin concentration, and antioxidant activity remain scarce. This study evaluated three extraction techniques and characterized antioxidant activity using 2,2-difenil-1-pikrilhidrazil (DPPH), azinobis(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS), and 4,6-tris(2-pyridyl)-s-triazine (FRAP) assays. Samples were vacuum-dried, ground, and subjected to oil extraction, followed by qualitative thin-layer chromatography and quantitative UV-Vis spectrophotometry. Soxhlet extraction yielded the greatest oil output, whereas maceration preserved astaxanthin more effectively due to the absence of thermal degradation. Cincalok exhibited the highest astaxanthin content (10.943 mg/g), followed by terasi and dried rebon. DPPH analysis indicated that cincalok oil possessed the strongest antioxidant activity (IC₅₀ 54.58 mg/L, Soxhlet), while dried rebon demonstrated the weakest. In contrast, ABTS and FRAP assays revealed lower responses for cincalok oil, suggesting that its primary antioxidant mechanism involves free-radical scavenging. These findings highlight cincalok as the most promising natural source of astaxanthin and local antioxidants, underscoring its potential for the development of coastal-based functional foods and health-promoting products.